The Leadership of the Kyai as a Conservative Instrument of the Islamic Boarding School (A Case Study at Pondok Pesantren Hidayatul Qur’an Banjarrejo) - Fitria, Norma (Nizham Jurnal Studi Keislaman, 2025)
This study explores the role of kyai leadership as a conservative force in preserving traditional values at Pondok Pesantren Hidayatul Qur’an Banjarrejo. In the face of modernization and social change, Islamic boarding schools (pesantren) are confronted with significant challenges to the continuity of their cultural heritage and value systems. As both spiritual and organizational leaders, kyai play a central role in maintaining the ideological stability of the pesantren through their charismatic authority, moral exemplarity, and adaptive strategies in response to change. Employing a qualitative approach with a case study design, this research utilizes in-depth interviews, participatory observation, and documentation. Thematic analysis is used to identify patterns of conservative kyai leadership and strategies for value preservation. The findings reveal that kyai internalize salafiyah values through religious rituals, the teaching of classical Islamic texts (kitab kuning), modest lifestyles, and the selective integration of technology. Kyai function as both guardians of tradition and adaptive agents who ensure the continuity of pesantren values amid a changing social landscape. This study fills a gap in the literature on pesantren conservatism and demonstrates that kyai leadership remains relevant and effective in confronting the pressures of modernity while upholding the cultural and spiritual integrity of the pesantren.